Eduplay Dashboard Application - Mohd Ridzwan, Elyn; Farid, Nur Haniesya; Misni, Fatin Syarina; Zulkifli, Nur Alyaa Nadia; Surachi, Norzilawati (2020)
As the use of technology evolves in education, an extensive range of new smart devices and digital applications is becoming available to academics. Eduplay Dashboard is an example of such technologies, which can help educators to improve the learning experience of their students inside and outside of the classroom. This app allows access to mediate and self-access services, as well as databases, online quizzes, go live, create game, slide presentation and etc. The project provides Mobile and Web-based application tools (apps) that allow online access for different users - students, instructors, and administrators. In addition, the app provides integrated all the existing free game based interactive learning platform and presentation tools into one center control.